2019
DOI: 10.1620/tjem.247.259
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tumor Necrosis Factor-<i>α</i> Promoter -308 G/A Polymorphism and Early Onset Sepsis in Preterm Infants

Abstract: Early-onset neonatal sepsis (EOS) is diagnosed during the first 7 days of neonatal life and is the major cause of morbidity and mortality among preterm infants. Genetic predisposition may have an impact on EOS susceptibility and outcome. The aim of our study was to explore the association between TNF-α-308 G/A or IL-6-174 G/C gene polymorphism and the susceptibility and outcome of EOS in preterm infants. The study included 471 preterm infants: 282 with EOS (151 with culture proven sepsis and 131 with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The current study showed that there is no statistically significant difference between IL-6 rs1800795 polymorphisms, indicating that the IL-6 rs1800795 G/C polymorphism had no significant association with the risk of sepsis in full-term neonates. Varljen et al 16 found no association between the genotypes or alleles of IL-6 rs1800795 G/C polymorphism and early-onset sepsis in premature infants, in agreement with the results of this study regarding full-term neonatal sepsis. The results of a meta-analysis by some researchers 17 18 showed that IL-6 rs1800795 G/C polymorphism was not associated with the risk or mortality of sepsis in any age or ethnic group.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that there is no statistically significant difference between IL-6 rs1800795 polymorphisms, indicating that the IL-6 rs1800795 G/C polymorphism had no significant association with the risk of sepsis in full-term neonates. Varljen et al 16 found no association between the genotypes or alleles of IL-6 rs1800795 G/C polymorphism and early-onset sepsis in premature infants, in agreement with the results of this study regarding full-term neonatal sepsis. The results of a meta-analysis by some researchers 17 18 showed that IL-6 rs1800795 G/C polymorphism was not associated with the risk or mortality of sepsis in any age or ethnic group.…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that there is no statistically significant difference between IL-6 rs1800795 polymorphisms, indicating that the IL-6 rs1800795 G/C polymorphism had no significant association with the risk of sepsis in full-term neonates. Varljen et al 16 found no association between the genotypes or alleles of IL-6 rs1800795 G/C polymorphism and early-onset sepsis in premature infants, in agreement with the results of this study regarding fullterm neonatal sepsis. The results of a meta-analysis by some researchers 17,18 showed that IL-6 rs1800795 G/C polymorphism was not associated with the risk or mortality of sepsis in any age or ethnic group.…”
Section: Discussionsupporting
confidence: 92%
“…25 It controls the promoters of nearly 200 genes stimulated by LPS and inflammatory factors, and its downstream genes such as IL-1b and IL-6 are involved in the development of sepsis. 26 Several studies [27][28][29] have reported increased TNF-a activity in sepsis models and the lung tissues of patients with sepsis. This activity is related to the severity of lung injury, so inhibiting TNF-a expression effectively inhibits the downstream signaling pathway, thus reducing lung injury and improving the survival rate.…”
Section: Discussionmentioning
confidence: 99%